Registration of 'CP 12‐1753' sugarcane. Issue 1 (28th September 2021) - Sood, Sushma; Momotaz, Aliya; Davidson, R. Wayne; Islam, Md S.; Sandhu, Hardev; Zhao, Duli; Baltazar, Miguel; Gordon, Vanessa S.; McCord, Per; Arbelo Coto, Orlando
Abstract: 'CP 12‐1753' (Reg. no. CV‐203, PI 698657) sugarcane (complex hybrid of Saccharum spp.) cultivar was developed through a cooperative research between USDA‐ARS, the Florida Sugar Cane League, Inc., and the University of Florida. It was derived from a polycross made at Canal Point, FL, on 8 Dec. 2010 between a female parent CP 08‐2409 and several male parents. CP 12‐1753 had 11 harvests in Stage 4: plant cane and first ratoon at four locations and second ratoon at three locations. Harvest data showed that CP 12‐1753 had significantly ( P ≤ .05) higher cane yield and economic index than the reference cultivars 'CL 88‐4730' and 'CPCL 97‐2730', respectively, but had significantly lower cane yield in plant cane and lower economic index than the reference cultivar 'CP 96‐1252'. Freeze tolerance of CP 12‐1753 was lower than the reference cultivars. CP 12‐1753 possesses Bru 1, a major gene for brown rust resistance, and showed resistance to brown rust. At the time of release, it was resistant to orange rust, mosaic, and smut. It was moderately resistant to leaf scald and ratoon stunting disease. Considering the agronomic, yield, and disease traits, CP 12‐1753 was released by the Florida Sugarcane Variety Committee in June 2020 to growers for commercial use on mineral (sand) soils. Core Ideas: Sugarcane cultivar CP 12‐1753 was released for Florida mineral soil. CP 12‐1753 has comparable yield to the reference cultivars. CP 12‐1753 has comparable or better disease resistance than the reference cultivars.